Trust and Satisfaction: The Hidden Drivers of QRIS Adoption and Long-Term Use Among Generation X in Indonesia - Imam Wicaksono (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the key factors influencing the continuance use intention of QR code-based payment systems (QRIS) among Generation X consumers in Indonesia, addressing the need for sustainable digital payment adoption. By extending the Technology Acceptance Model (TAM) and the Expectation-Confirmation Theory (ECT), the research explores how perceived ease of use, perceived usefulness, trust, and satisfaction affect continued engagement with QRIS. A quantitative approach was employed, with data collected from 217 respondents who have used QRIS within the past three months. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to assess the relationships among the constructs, utilizing bootstrapping to determine the significance of the path coefficients. The analysis revealed that perceived ease of use significantly influences both perceived usefulness and user satisfaction, which in turn positively impacts trust. Interestingly, while trust was a significant predictor of continuance intention, satisfaction and perceived usefulness did not directly lead to continued usage, challenging traditional assumptions in the literature. This highlights the complex interplay of factors that drive continued engagement with QRIS. This research contributes to the digital payment literature by integrating perceived ease of use, perceived usefulness, trust, and satisfaction into a comprehensive model of continuance intention. It offers both theoretical insights and practical guidance for stakeholders in the rapidly evolving digital payment industry, particularly within the context of QRIS adoption, especially among Generation X in Indonesia.